Effect of Physical Activity on Cognitive Development: Protocol for a 15-Year Longitudinal Follow-Up Study. (28th September 2017) - Zhao, Guanggao; Quan, Minghui; Su, Liqiang; Zhang, Hanbin; Zhang, Jiayi; Zhang, Jinming; Fang, Hui; Cao, Zhen-Bo; Zhu, Zheng; Niu, Zhanbin; Wang, Ru; Chen, Peijie
Abstract : The aim of the study is to investigate the relationship between physical activity as assessed by accelerometers and cognitive development across the human age ranges (from children and adolescents to adults). Additionally, this study seeks to explore whether physical activity contributes to cognitive development via modification of plasma insulin-like growth factor 1 (IGF-1) and brain-derived neurotrophic factor (BDNF). In the study, 500 preschool children (3.5–5.5 years old) are taking part in 6 triennial assessment waves over the span of 15 years. At each wave, participant measures included (a) 7-day physical activity monitoring using ActiGraph's GT3X accelerometers, (b) the evaluation of cognitive development, (c) anthropometric and physical fitness assessments, (d) plasma IGF-1 and BDNF concentrations, and (e) retrospective questionnaires. Linear regression models are used to examine the effect of physical activity on cognitive development; plasma IGF-1 and BDNF concentrations are considered as mediators into data analyses. The results of the study may help to inform future health interventions that utilize physical activity as a means to improve cognitive development in children, adolescents, and adults. Additionally, the study may assist in determining whether the putative effects occur via modification of plasma IGF-1 or BDNF concentrations.